Eight years of IMRT quality assurance with ionization chambers and film dosimetry: experience of the montpellier comprehensive cancer center - Dubois Jean-Bernard; Riou Olivier; Aillères Norbert; Laliberté Benoit; Fenoglietto Pascal; Azria David (Radiation Oncology, 2011)
Abstract Background To present the results of quality assurance (QA) in IMRT of film dosimetry and ionization chambers measurements with an eight year follow-up. Methods All treatment plans were validated under the linear accelerator by absolute and relative measures obtained with ionization chambers (IC) and with XomatV and EDR2 films (Kodak). Results The average difference between IC measured and computed dose at isocenter with the gantry angle of 0° was 0.07 ± 1.22% (average ± 1 SD) for 2316 prostate, 1.33 ± 3.22% for 808 head and neck (h&n), and 0.37 ± 0.62% for 108 measurements of prostate bed fields. Pelvic treatment showed differences of 0.49 ± 1.86% in 26 fields for prostate cases and 2.07 ± 2.83% in 109 fields of anal canal. Composite measurement at isocenter for each patient showed an average difference with computed dose of 0.05 ± 0.87% for 386 prostate, 1.49 ± 1.86% for 158 h&n, 0.37 ± 0.34% for 23 prostate bed, 0.80 ± 0.28% for 4 pelvis, and 2.31 ± 0.56% for 17 anal canal cases. On the first 250 h&n analyzed by film in absolute dose, the average of the points crossing a gamma index 3% and 3 mm was 93%. This value reached 99% for the prostate fields. Conclusion More than 3500 beams were found to be within the limits defined as validated for treatment between 2001 and 2008.